Kata Kunci “Halal dan Haram dalam Islam” pada Dimensions - Khalishah Sajidah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the dimensions with the keyword religious moderation. This study uses a bibliometric dimensions technique. The formal object of this study is dimensions, while the material object is dimensions analysis with the keyword halal and haram in Islam. The results and discussion of this study indicate that there are four categories in the mapping research of halal and haram in Islam. First, the research category in the publication of articles on halal and haram in Islam. Second, the development of publications (overview) regarding halal and haram in Islam. Third, researchers who play an active role in halal and haram in Islam. And fourth, the publication places that dominate publications regarding halal and haram in Islam.